2007
DOI: 10.1002/cncr.22672
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of regional, hepatic intra‐arterial paclitaxel in patients with breast carcinoma metastatic to the liver

Abstract: Objective To examine health disparities as a function of ethnicity using data from LUpus in MInorities, NAture versus nurture (LUMINA), a longitudinal study of patients with systemic lupus erythematosus (SLE); to build an explanatory model of how ethnic disparities occur in this setting; and to suggest appropriate interventions. Methods LUMINA patients (meeting American College of Rheumatology criteria for SLE) ages ≥16 years of African American, Hispanic (from Texas), Hispanic (from Puerto Rico), or Caucasian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…46). Previous studies showed that the administration of paclitaxel directly into the hepatic artery resulted in a 95% mean hepatic extraction rate during the infusion and a 61% mean extraction rate from 5 to 9 hours after completion of the infusion (16,47). In contrast, this trial showed approximately a 42% mean hepatic extraction rate following HAI nab-paclitaxel when administered over a 60-minute period of time.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…46). Previous studies showed that the administration of paclitaxel directly into the hepatic artery resulted in a 95% mean hepatic extraction rate during the infusion and a 61% mean extraction rate from 5 to 9 hours after completion of the infusion (16,47). In contrast, this trial showed approximately a 42% mean hepatic extraction rate following HAI nab-paclitaxel when administered over a 60-minute period of time.…”
Section: Discussionmentioning
confidence: 60%
“…Different agents have been used to treat hepatic metastasis from various tumor types: cisplatin (6-9), oxaliplatin (10)(11)(12)(13)(14), paclitaxel (15,16), floxuridine (FUDR; refs. (17)(18)(19)(20)(21), interleukin-2 (22, 23), 5-fluorouracil/leucovorin (24), and IFN (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to deliver higher concentrations of cytotoxic drugs to isolated tumor sites makes regional chemotherapy a possible alternative in patients with single metastatic foci, especially if not amenable to other local treatments. Small case series of regional hepatic intra-arterial therapy in patients with liver metastases from breast cancer have been reported (Camacho et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Published data suggest that TACE may have a palliative role in delaying progression of isolated LiM. There is currently only scarce data regarding its role in the management of MBC, but tumor shrinkage can be dramatic and may render patients candidates for liver resection with curative intent, potentially resulting in long-term disease-free survival [50]. In the published series, TACE commonly follows progression under ST: a recent study compared combined TACE and ST for liver-only metastases (n = 44) to ST alone (n = 43).…”
Section: Local Treatment Of Selected Disease Sitesmentioning
confidence: 99%